Vacuum Evaporation of High-Quality CsPbBr3 Thin Films for Efficient Light-Emitting Diodes - Tianxinyu Bai; Shenwei Wang; Liyuan Bai; Kexin Zhang; Chunyang Chu; Lixin Yi (Nanoscale Research Letters, 2022)
Abstract The all-inorganic lead halide perovskite has become a very promising optoelectronic material due to its excellent optical and electrical properties. Device performances are currently hindered by crystallinity of the films and environmental stability. Here, we adopted dual-source co-evaporation method to prepare CsPbBr3 films. By adjusting and controlling the co-evaporation ratio and substrate temperature, we obtained CsPbBr3 films with large grain sizes and uniform morphology. Films with smooth surfaces and large grains exhibit properties such as efficient photon capture, fast carrier transport, and suppressed ion migration. Therefore, in this paper, by refining the annealing conditions, the effects of annealing temperature and time on the films were studied in detail. The CsPbBr3 films were annealed under suitable annealing temperature and time in ambient air, and films with high quality and crystallinity and average grain size up to ~ 2.5 μm could maintain stability in ambient air for 130 days. The corresponding LEDs show the full width at half maximum (FWHM) of the green EL spectrum is as narrow as 18 nm, and the devices have a low turn-on voltage V T ~ 3 V and can work continuously for 12 h in ambient air.